2021
DOI: 10.1037/pag0000614
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional factors account for age differences in self-reported mind-wandering.

Abstract: The present study investigated the contribution of dispositional factors in accounting for the perplexing negative relationship between aging and mind-wandering (MW). First, we sought to examine whether experimentally manipulating participants' motivation during a modified Sustained Attention to Response Task (SART) would modulate sustained attention performance and MW reports for younger and older adults. Results indicated that a performance-based motivational incentive influenced self-reported motivation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
(78 reference statements)
3
16
0
Order By: Relevance
“…Regarding the age/mind-wandering paradox, the present results were largely consistent a subjective and dispositional account (Jackson & Balota, 2012; Krawietz et al, 2012; Moran et al, 2021; Nicosia & Balota, 2021; Seli et al, 2021). Older adults reported fewer TUTs than younger adults.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the age/mind-wandering paradox, the present results were largely consistent a subjective and dispositional account (Jackson & Balota, 2012; Krawietz et al, 2012; Moran et al, 2021; Nicosia & Balota, 2021; Seli et al, 2021). Older adults reported fewer TUTs than younger adults.…”
Section: Discussionsupporting
confidence: 88%
“…Further, Krawietz et al (2012) found that including interest as a covariate eliminated the age difference in mind-wandering. Frank et al (2015) and Seli et al (2021) reported that participants’ motivation partially mediated the relationship between age and mind-wandering, and Nicosia and Balota (2021) found that self-reported conscientiousness, interest, and motivation fully mediated the relationship between age and mind-wandering. Thus, it is possible that dispositional factors may explain age differences in mind-wandering, although the physiological mechanisms through which this is achieved remain unclear.…”
mentioning
confidence: 99%
“…Ultimately, the present set of studies suggests that MW may indeed serve the important role of allowing for offline replay of recently encoded information when we are awake but engaged in a minimally demanding task. This functional role of MW may help resolve the tension in the literature regarding the cognitive consequences of the paradoxical result of reduced MW in older adults compared with younger adults (Maillet & Schacter, 2016; see Nicosia & Balota, 2021; for a discussion on possible mechanisms of age differences in MW). The operations that occur as a result of this age-related decline in MW may contribute to age-related deficits in episodic memory retrieval and potentially consolidation as well.…”
Section: Discussionmentioning
confidence: 96%
“…Given recent demonstrations that the benefits of wakeful rest on retention are moderated by the presence of intermediate retrieval tests [ 51 ], as well as working memory capacity [ 52 ], it is possible that the age-dependent results reported by Martini and colleagues [ 44 ] are driven by factors related to test expectancy and/or working memory maintenance, which would be more likely to occur in the context of intentional, as opposed to incidental encoding. Indeed, older adults might be more conscientious and/or motivated to perform well on the memory task, as compared to younger adults [ 69 , 70 ], but of course, other studies have found that older adults are less likely to initiate effective memory strategies [ 71 , 72 , 73 , 74 ]. In the present study, we did not notice a consistent pattern of age differences in self-reported test expectancy in Experiment 1 (Younger: 20.6% vs.…”
Section: Discussionmentioning
confidence: 99%